2010
DOI: 10.1016/j.ajhg.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Systems Genetics Analysis of Gene-by-Environment Interactions in Human Cells

Abstract: Gene by environment (GxE) interactions are clearly important in many human diseases, but they have proven to be difficult to study on a molecular level. We report genetic analysis of thousands of transcript abundance traits in human primary endothelial cell (EC) lines in response to proinflammatory oxidized phospholipids implicated in cardiovascular disease. Of the 59 most regulated transcripts, approximately one-third showed evidence of GxE interactions. The interactions resulted primarily from effects of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 56 publications
3
103
1
1
Order By: Relevance
“…A number of studies surveyed transcriptional genotype-byenvironment interactions in humans and reported dozens of response eQTLs in vitro under a variety of environmental challenges such as radiation (26) and treatment with various agents (27)(28)(29). The number of interacting loci in response to malaria infection in our in vivo study is lower than the number of response eQTLs reported in these studies despite the fact that similar sample sizes were used.…”
Section: Resultscontrasting
confidence: 52%
“…A number of studies surveyed transcriptional genotype-byenvironment interactions in humans and reported dozens of response eQTLs in vitro under a variety of environmental challenges such as radiation (26) and treatment with various agents (27)(28)(29). The number of interacting loci in response to malaria infection in our in vivo study is lower than the number of response eQTLs reported in these studies despite the fact that similar sample sizes were used.…”
Section: Resultscontrasting
confidence: 52%
“…However, when the cells were stimulated with oxidized lipids, all cells reached a similar level of HO-1 mRNA, regardless of basal levels of HMOX1 transcript (43). We propose that miRNAs may be serving as a rheostat to titrate the levels of HO-1 expression to a physiologic set point (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SNP genotyping was performed using the Affymetrix SNP 6.0 microarray platform as described previously ( 15 ). Microarray images were processed using the Affymetrix Genotyping Console 4.1 to make the SNP calls.…”
Section: Genotyping and Association Analysismentioning
confidence: 99%